SOCIAL SCIENCE EDUCATION AND SELF-RELIANCE IN THE 21st CENTURY NIGERIA - Sule, Matthew Nshim (Sokoto Educational Review, 2018)
The paper examines the concept of social science education as a distinct study area of knowledge. It equally identifies and highlights the major areas of social science education and discusses their general objectives for societal development. Specifically, it addresses the question of self-relience among graduates of tertiary institutions especially university graduates. Reasonably, it was discovered that social science education graduates appears to be non-conformists to agreed value as the empirical aspects of the study suggest. Suggestions for improving the teaching of social science education teaching were made. Some of the suggestions include the improvement of the quality of basic education, enhancement of the remuneration of teachers at all levels of education, teaching to be targeted at career relevance and the employability of graduates as well as lhe implementation of quality assurance measures for the maintenance of standards.